Acyl homoserine lactone changes the abundance of proteins and the levels of organic acids associated with stationary phase in Salmonella Enteritidis. (January 2017) - de Almeida, Felipe Alves; Pimentel-Filho, Natan de Jesus; Carrijo, Lanna Clícia; Bento, Cláudia Braga Pereira; Baracat-Pereira, Maria Cristina; Pinto, Uelinton Manoel; de Oliveira, Leandro Licursi; Vanetti, Maria Cristina Dantas
Abstract: Quorum sensing (QS) is cell-cell communication mechanism mediated by signaling molecules known as autoinducers (AIs) that lead to differential gene expression. Salmonella is unable to synthesize the AI-1 acyl homoserine lactone (AHL), but is able to recognize AHLs produced by other microorganisms through SdiA protein. Our study aimed to evaluate the influence of AI-1 on the abundance of proteins and the levels of organic acids of Salmonella Enteritidis. The presence of N -dodecyl-homoserine lactone (C12-HSL) did not interfere on the growth or the total amount of extracted proteins of Salmonella . However, the abundance of the proteins PheT, HtpG, PtsI, Adi, TalB, PmgI (or GpmI), Eno, and PykF enhanced while the abundance of the proteins RplB, RplE, RpsB, Tsf, OmpA, OmpC, OmpD, and GapA decreased when Salmonella Enteritidis was anaerobically cultivated in the presence of C12-HSL. Additionally, the bacterium produced less succinic, lactic, and acetic acids in the presence of C12-HSL. However, the concentration of extracellular formic acid reached 20.46 mM after 24 h and was not detected when the growth was in the absence of AI-1. Considering the cultivation period for protein extraction, their abundance, process and function, as well as the levels of organic acids, we observed in cells cultivated in presence of C12-HSL a correlation with what is described in the literature as entry into the stationary phase of growth, mainly related to nitrogen and amino acid starvation and acid stress. Further studies are needed in order to determine the specific role of the differentially abundant proteins and extracellular organic acids secreted by Salmonella in the presence of quorum sensing signaling molecules. Highlights: AHL-based quorum sensing changes the protein abundance of Salmonella Enteritidis. AHL-based quorum sensing influences the levels of organic acids of Salmonella Enteritidis. The abundance of proteins associated with stationary phase of Salmonella Enteritidis was altered in the presence of AHL. The level of extracellular formate was altered in Salmonella Enteritidis growing in presence of AHL.